2010
DOI: 10.1051/0004-6361/200913879
|View full text |Cite
|
Sign up to set email alerts
|

The outflow in Mrk 509

Abstract: We analyzed three XMM-Newton observations of the Seyfert 1 galaxy Mrk 509, with the goal of detecting small variations in the ionized outflow properties. Measurements such as these are limited by the quality of the cross-calibration between RGS, the best instrument for characterizing the spectrum, and EPIC-pn, the best instrument for characterizing the variability. For all three observations we are able to improve the relative calibration of RGS and pn consistently to 4%. In all observations we detect three di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2011
2011
2012
2012

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 28 publications
3
26
1
Order By: Relevance
“…A simultaneous fit to the pn and RGS data of these spectra showed three ionisation components that correspond to our components B, C, and a blend of D and E. Components B and C did not show any significant variability between the observations. The fits of Detmers et al (2010) indicate that the ionisation parameter for component D/E had decreased from 3.29 ± 0.04 in the first observation of 2005 to 3.01 ± 0.06 in the 2006 observation. From this change within 0.5 year an upper limit to the distance of 0.5 pc was derived.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A simultaneous fit to the pn and RGS data of these spectra showed three ionisation components that correspond to our components B, C, and a blend of D and E. Components B and C did not show any significant variability between the observations. The fits of Detmers et al (2010) indicate that the ionisation parameter for component D/E had decreased from 3.29 ± 0.04 in the first observation of 2005 to 3.01 ± 0.06 in the 2006 observation. From this change within 0.5 year an upper limit to the distance of 0.5 pc was derived.…”
Section: Discussionmentioning
confidence: 95%
“…Our present estimates are more direct. Detmers et al (2010) analysed the XMM-Newton spectra of Mrk 509 taken in 2005 and 2006. A simultaneous fit to the pn and RGS data of these spectra showed three ionisation components that correspond to our components B, C, and a blend of D and E. Components B and C did not show any significant variability between the observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both sources, the presence of a warm absorber was confirmed, and its features could explain the residuals of the fit. The most complete studies of the warm absorber of these two objects were done using XMM/RGS data by Smith et al (2007) and Detmers et al (2010) for Mrk 509, and by Longinotti et al (2010) for Mrk 841.…”
Section: Additional Contribution Of the Warm Absorbermentioning
confidence: 99%
“…Using Ginga, Singh et al (1990) revealed a hardening of the power law at energies greater than 10 keV. BeppoSAX observations (Perola et al 2000) showed a power-law cut-off at 70 keV and revealed information about the warm absorber (Dadina et al 2005), which since has been studied in depth by Smith et al (2007) and Detmers et al (2010), with XMM-Newton/RGS data. Ponti et al (2009) presented the most complete study to date of the Fe K complex, using XMM-Newton data and the same Suzaku observations we present here.…”
Section: Introductionmentioning
confidence: 96%